Case report: Boundaries of oncological and traumatological medical care in ancient Egypt: new palaeopathological insights from two human skulls - Tondini, Tatiana; Isidro, Albert; Camarós, Edgard (Frontiers in Medicine, 2024)
The present case studies report malignant neoplastic and traumatic lesions observed on two ancient Egyptian skulls held at the Duckworth Collection (Cambridge University). The analysis aims to characterise the lesions and provide a diagnosis using a methodology based on micro-CT scanning and microscopic bone surface analysis. Results pointed towards neoplastic lesions in both cases and healed severe skull trauma in one of them suggesting successful traumatological therapy. Interestingly, our analysis has identified the presence of perimortem cutmarks associated with metastatic lytic lesions in one of the skulls, indicating a potential surgical treatment attempt or postmortem medical exploration. We argue that the two cases, although not contemporary, allow a palaeopathological discussion on oncological and traumatological understanding and management of such conditions in the past. The confrontation of two potential managements represented by two different types of lesions represent a clear boundary in ancient Egyptian medical care and a milestone in the history of medicine.